Kajian Filsafat Ontologi Martin Heidegger atas Simbol Sengsara dalam Kongregasi Pasionis dan Maknanya bagi Kehidupan Iman Kristiani - Ton, Sekundus Septo Pigang; Zandro, Agrindo; Pandor, Pius; Lein, Lusia Lutok (Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
This article seeks to investigate Martin Heidegger’s ontological philosophy in connection with the symbols of suffering present in the Passionist Congregation and their significance for Christian faith. The article follows a structured literature review approach, examining a range of sources such as Karl Rahner’s Foundations of Christian Faith: An Introduction to the Idea of Christianity, Louis-Marie Chauvet’s Symbol and Sacrament, as well as other works discussing Heidegger’s ontological philosophy like Armada Riyanto’s Relasionalitas and F. Budi Hardiman’s Heidegger and the Mysticism of Everyday Life: An Introduction to Sein und Zeit. Through this analysis, it is revealed that the symbols of suffering within the Passionist Congregation function as a